Connecting pixels to trust: a systematic review of the relationship between government social media usage and citizens' trust in government - Chi, Jinglin; Kamarudin, Syafila; Abdul Rahman, Saiful Nujaimi (Redfame Publishing Inc., 2024)
Government social media has garnered significant attention due to its impact on citizens' attitudes, prompting extensive academic research. This review aims to delineate a decade-spanning corpus of literature, discern prevalent research trends, and propose a prospective research agenda in this domain. Employing systematic literature review and PRISMA methodologies, our investigation identified 22 published articles through comprehensive keyword searches across Scopus, Google Scholar, CNKI, and ProQuest databases, ensuring a diverse representation of geographic areas to capture the global perspective on this issue. This study mainly utilize a mixed research methodology encompassing bibliometrics and content analysis to analyze data results. This paper conducted a bibliometric analysis revealing that the relationship between government social media usage and citizens' trust in the government remains a contentious topic. To delve deeper into this relationship, the selected literature were categorized into three distinct research themes through content analysis, forming a comprehensive conceptual framework. Upon meticulous analysis, the findings suggest that future research should explore the communication field more extensively, encompass a broader range of research topics, employ refined concepts, and examine the mediating role of audience behavior, particularly focusing on the behavior of young people. Furthermore, researchers are encouraged to adopt a more thorough and detailed systematic approach when reviewing relevant literature on government social media.